2016
DOI: 10.4025/psicolestud.v21i2.30660
|View full text |Cite
|
Sign up to set email alerts
|

O Outro Lado Da Porta Giratória: Apoio Comunitário E Saúde Mental

Abstract: A Reforma Psiquiátrica tem como princípio fundamental o cuidado em liberdade e prevê a internação breve em hospital geral apenas quando esgotados os recursos extra-hospitalares. No entanto, as múltiplas reinternações em unidades psiquiátricas ainda são comuns no cotidiano hospitalar. O foco desse estudo está no que acontece para além dos portões do hospital, analisando elementos da vida comunitária dos portadores de sofrimento psíquico e se essas experiências se relacionam de alguma forma com a frequente neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
2
0
7
Order By: Relevance
“…This is in line with the literature review, which points to lack of contact with the family as a risk factor for readmissions (Bezerra & Dimenstein, 2011;Roick et al, 2004) and having social support as a protective factor (Donisi et al, 2016). In the same sense, the study by Silveira, Rocha, Rocha and Zanardo (2016), conducted with users, pointed out the importance of community and family as sources of bonding and support, and the feeling of belonging in that environment. The authors found that users with a larger number of psychiatric hospitalizations considered that they did not have a very close relationship to the community when compared to those with fewer hospitalizations.…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with the literature review, which points to lack of contact with the family as a risk factor for readmissions (Bezerra & Dimenstein, 2011;Roick et al, 2004) and having social support as a protective factor (Donisi et al, 2016). In the same sense, the study by Silveira, Rocha, Rocha and Zanardo (2016), conducted with users, pointed out the importance of community and family as sources of bonding and support, and the feeling of belonging in that environment. The authors found that users with a larger number of psychiatric hospitalizations considered that they did not have a very close relationship to the community when compared to those with fewer hospitalizations.…”
Section: Discussionsupporting
confidence: 81%
“…Estudo 26 realizado neste mesmo hospital apontou para taxa de readmissões em 29,17%. Somado a isso, quanto mais internações psiquiátricas, maior a probabilidade reinternação 27 .…”
Section: Discussionunclassified
“…Our results were close to those of other authors, because in rural areas or those with less supply, the level of burden and even mortality was higher compared to large cities or those with greater prosocial leisure opportunities, diversified offer or recreational areas. The community is highly important for the collective development and welfare, therefore, the creation of social support networks improves the quality of life and mental health of its members (30) .…”
Section: Discussionmentioning
confidence: 99%